Revving Up Autotronics: Unleashing Content, Technical, and Pedagogical Power Through a Diesel Rotary Injection Pump Mock-Up (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study develops and evaluates a diesel rotary injection pump mock-up as a pedagogical innovation to bridge the gap between theoretical instruction and hands-on experience in automotive technology programs. The mock-up simulates key diesel fuel injection functions through manipulable components, addressing resource constraints in laboratories. Employing a descriptive quantitative pre-test–post-test design, 30 BS Autotronics students, 5 teachers from University of Science and Technology of Southern Philippines (USTP), and 3 automotive experts from Toyota/Isuzu Motors rated its content, technical, and pedagogic quality via a validated 15-item, 5-point Likert scale instrument. Post-test means ranged 4.6–4.8, reflecting strong agreement on accuracy, reliability, safety, and instructional alignment, with minor concerns on usability and sustained engagement. Wilcoxon Signed-Rank tests across all parameters showed W = 0, Z = -5.37 (p < .001), and large effect sizes (r = 0.87), confirming highly significant, unanimous positive shifts in perceptions with substantial practical impact. These findings validate the mock-up as a cost-effective tool enhancing autotronics education, better preparing students for industry diesel maintenance while highlighting areas for usability refinement.